2015
DOI: 10.1002/ajmg.a.37083
|View full text |Cite
|
Sign up to set email alerts
|

TCF12 microdeletion in a 72‐year‐old woman with intellectual disability

Abstract: Heterozygous mutations in TCF12 were recently identified as an important cause of craniosynostosis. In the original series, 14% of patients with a mutation in TCF12 had significant developmental delay or learning disability. We report on the first case of TCF12 microdeletion, detected by array‐comparative genomic hybridization, in a 72‐year‐old patient presenting with intellectual deficiency and dysmorphism. Multiplex ligation‐dependent probe amplification analysis indicated that exon 19, encoding the function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…Two follow-up studies have confirmed the importance of TCF12 mutations in coronal craniosynostosis, both in the context of familial mutations [37], and in a more general screen of craniosynostosis [29]. Given the haploinsufficiency mechanism of TCF12 mutations, heterozygous deletions are also expected to be pathogenic and this has been confirmed in two reports [38, 39]. At present, diagnostic labs rely on DNA sequencing to test TCF12 , pointing to the need for a dedicated diagnostic method such as multiplex ligation-dependent probe amplification (MLPA) to detect TCF12 deletions.…”
Section: Non-syndromic Craniosynostosismentioning
confidence: 84%
“…Two follow-up studies have confirmed the importance of TCF12 mutations in coronal craniosynostosis, both in the context of familial mutations [37], and in a more general screen of craniosynostosis [29]. Given the haploinsufficiency mechanism of TCF12 mutations, heterozygous deletions are also expected to be pathogenic and this has been confirmed in two reports [38, 39]. At present, diagnostic labs rely on DNA sequencing to test TCF12 , pointing to the need for a dedicated diagnostic method such as multiplex ligation-dependent probe amplification (MLPA) to detect TCF12 deletions.…”
Section: Non-syndromic Craniosynostosismentioning
confidence: 84%
“…The potential role of dlx5a in development and morphogenesis of non-skeletal craniofacial tissues in fish has not been investigated so far. The second transcription factor, tcf12 , encodes another member of bHLH E-protein family and plays role in cranio-skeletal development; particularly in the morphogenesis of the frontal bone and cranial vault thickening in mammals 8284 . Similar to dlx5a , the potential role of tcf12 in development and morphogenesis of non-skeletal craniofacial tissues has yet to be studied in fish.…”
Section: Discussionmentioning
confidence: 99%
“…Although 81% of the individuals with TCF12 mutations presented with apparent cNCS, some of the affected individuals had developmental delays and dysmorphic features overlapping with the Saethre-Chotzen syndrome [Sharma et al, 2013]. More recently, the phenotypic spectrum of TCF12 mutations has been extended to include possible facial and limb anomalies, and intellectual disability [Di Rocco et al, 2014; Le Tanno et al, 2014; Paumard-Hernandez et al, 2015; Piard et al, 2015]. Based on these observations, it is reasonable to recommend TCF12 testing for all patients with cCS, with or without associated anomalies.…”
Section: Genetic Etiopathogenesis Of Craniosynostosismentioning
confidence: 99%